Content of care of student youth and children in activity of Ukrainian communities at Bukovina (end of XIX – 1914) - Zvozdetska, Valentyna (ScienceRise: Pedagogical Education, 2020)
The article elucidates the activity of Ukrainian communities at Bukovina of the second half of XIX to the end of the Austrian-Hungarian period (“Rusin Talk”, “Rusin Rada”, “Folk house”, “Rusin school”, “Sych”, “Myronosistsy”, “Women association” and others) in the sphere of social care over children and youth. The special attention is paid to one of great and long-term project – opening and keeping of bursas (dormitories for poor students and natives of rural territories). Causes of the necessity of such institutions are elucidated, the contingent of students, lived in bursas, financing sources, forms of costs involvement for provision and keeping of the institutions, content, forms and directions of learning-upbringing work, realized in bursas, also content of work and a circle of duties of workers of such institutions are described. The article substantiates the importance of bursas functioning for forming national consciousness by involving students in different types of educative work. Form and types of social support and help, such as: cloth and accommodation supply for poor students, opening and keeping of bursas (dormitories); textbook and school accessories supply; monetary “address” payments for poor students, organization of free food for them; help for sick persons; orphan house support are concretized. The activity of communities and separate famous persons in Bukovina in organization of the system of payments for charity projects and creation of special funds is noted. Based on studying archive documents, materials of periodicals, special literature, the review of concrete cases of the charity direction, realized by Ukrainian communities at Bukovina in the studied period, is presented